Liberalization and financial sector competition: a critical contribution to the empirics with an African assessment - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2013)
This paper investigates how financial, trade, institutional and political liberalization policies have affected financial sector competition in Africa using updated data to appraise second generation reforms. The 'freedom to trade' and 'economic freedom' indices are employed. Hitherto, unexplored financial sector concepts of formalization, semi-formalization, informalization and non-formalization are also introduced. The following findings are established. Firstly, relative to money supply: (1) with the exception of the economic freedom mechanism, liberalization policies have generally decreased the growth of the formal financial sector to the benefit of other financial sectors; (2) apart from the foreign direct investment and economic freedom channels, liberalization policies have been fruitful for semi-formal financial development at the cost of other financial sectors and; (3) with the exception of economic freedom, both the informal and non-formal sectors have developed owing to liberalization to the detriment of the formal financial sector. Secondly, relative to GDP, the semi-formal, informal and/or non-formal financial sectors have also generally improved as a result of liberalization. Policy implications are discussed.
Keywords: D60; E50; F30; O17; O55; 330; Welfare; Banking; Liberalization; Shadow economy; Africa